Occupational exposure to ketamine detected by hair analysis: a retrospective and prospective toxicological study. (August 2016) - Favretto, D.; Vogliardi, S.; Tucci, M.; Simoncello, I.; El Mazloum, R.; Snenghi, R.
Highlights: 11 veterinary physicians were recruited on voluntary base. They were all using ketamine as an anaesthetic in surgery. A prospective study was performed on two naïve subjects. Ketamine and norketamine were detected in head and pubic hair. The possibility of unaware exposure to ketamine was demonstrated. Abstract: Ketamine (KT) is used to induce and maintain general anaesthesia in combination with sedative drugs in human and animals. Because of its dissociative and hallucinogenic effects, KT has become a recreational drug in a variety of social settings and may be included in the panel of drugs of abuse that are controlled in driving under the influence (DUI) ascertainment. In a local driving license re-granting protocol, a case where a veterinary physician was found positive to KT and nor-ketamine (NK) in hair suggested the possibility of a professional exposure in a veterinary setting and prompted an experimental study. Male (7) and female (4) veterinary physicians were recruited on a voluntary base. Detailed information was collected on their habits, use of drugs, professional practice, frequency and mode of using KT injections. Hands and skin were examined. Head hair and pubic hair were collected. Two naïve subjects, starting their professional practice at a local veterinary clinic, were recruited and their hair (head, pubic, axillary, thoracic hair, and beard) and urine were collected before and after usual clinic activity. Hair were cut according to their length, washed, pulverized and 25 mg were extracted and analyzed by liquid chromatography coupled to high accuracy, high resolution mass spectrometry. All the hair samples from the veterinary physicians turned to be positive for KT, at a concentration varying from 0.010 to 0.840 ng/mg in head hair and from 0.040 to 2.04 ng/mg in pubic hair; NK ranged from not detected to 0.080 ng/mg in head hair, from not detected to 0.100 in pubic hair; when KT was ≥0.100, NK was always detected. For the two naïve subjects, hair from different body sites were negative before they started their activity, and positive one month later; some urine samples resulted positive and confirmed systemic exposure to KT. The possibility of unaware exposure to KT was demonstrated. The site of absorption is skin, independently from the presence of skin injuries due to hand contact with KT injection solutions and/or animal body fluids by veterinary physicians during clinical activities and animal handling. Possible adverse systemic effects by unaware KT exposure need to be studied and concerns have arisen as to healthy and safe workplace policies. Comparison with a population of subjects undergoing driving license re-granting evidenced a larger range of concentration in this latter setting (0.050–10.0 ng/mg for KT, not detected to 0.100 ng/mg for NK).